Syed Sheikh Ahmad Al-Fatani: Peletak Dasar Reformasi Pendidikan dan Modernisme di Alam Melayu - Kiki Wiyandi; Nurkholis Ramdhani; Anisatul Mardiah; Muhammad Noupal (WISE Pendidikan Indonesia, 2026)
Syed Sheikh Ahmad bin Muhammad Zain Al-Fatani (1856-1908) is recognized as one of the most significant Muslim intellectuals from the Malay Archipelago whose educational thought has profoundly influenced the transformation of Islamic education in Southeast Asia. This article examines Al-Fatani's educational philosophy within the framework of reform and modernism, employing a historical-philosophical analysis of his major works and intellectual network. The study finds that Al-Fatani laid crucial groundwork for transforming the traditional pondok (Islamic boarding school) system into a more structured, rational, and contextually responsive educational model. His reformist ideas encompass three main dimensions: (1) a critical reassessment of the traditional dichotomy between religious and secular knowledge, advocating instead for an integrated curriculum that combines revealed and rational sciences; (2) the modernization of pedagogical methods, emphasizing gradual learning (tadrij), logical reasoning (qiyas and 'aql), and lifelong education; and (3) the empowerment of the Malay language (Jawi) as a legitimate medium for advanced Islamic scholarship, thereby democratizing access to knowledge. Al-Fatani's intellectual legacy demonstrates that Islamic educational reform in the Malay Archipelago did not emerge in the 20th century alone but was pioneered as early as the late 19th century through the scholarly networks of the Haramain (the two holy cities of Mecca and Medina). His integrated epistemology offers a relevant model for contemporary Islamic education, particularly in addressing the persistent dichotomy between religious and general education in Muslim societies.